A COMPARATIVE CLINICAL STUDY ON APPLICATION OF YASHADA BHASMA LEPA AND JATYADI GHRITA IN THE MANAGEMENT OF DUSHTA VRANA W.S.R. DIABETIC ULCER - Venkata Rajan B, Gnani; Savadi, *B. S. (International Journal of Ayurveda and Pharma Research, 2019)
Introduction: Wounds and their management are fundamental to the practice of surgery. In surgery of trauma, wound is frequently a primary pathology. In elective surgery, it is through the wound that access is obtained to deal with the underlying pathology. In both situations surgeon’s task is to minimize the adverse effects of wound, remove or repair damaged structures and harness the process of wound healing to restore function.Objectives: The study is aimed to know the comparative efficacy of Yashada Bhasma Lepa and Jatyadi Ghrita in the management of Dushta Vrana.Method: Clinically diagnosed 30 patients of Dushta Vrana were randomly divided into two groups, each group consisting of 15 Patients. First (A group) is treated by Yashada Bhasma Lepa and second (B group) is treated by Jatyadi Ghrita for 21 days.Result: On the basis of assessment criteria and on the overall result of treatment the patients of Yashada Bhasma Lepa group showed better relief when compared to Jatyadi Ghrita.Interpretation: Yashada Bhasma Lepa having the properties of Tikta, Kashaya, Katu, Rasa predominance thus had action of Kapha Pitta Shamana, Netra Roga, Pandu, Bahumootra Roga, Kasa, Swasa, Rajayakshma, Ratrisweda, Vranasrava Avarodaka,Prameha, Sankochakara.etc. Thus this help for Shodhanaand Ropana.Conclusion: Yashada Bhasma Lepa has provided better relief in maximum signs and symptoms of the patients of Dushta Vrana, in comparison to Jatyadi Ghrita. Its overall effects were also better in comparison to Yashada Bhasma Lepawith Jatyadi Ghrita and dressing reduces the infection.